Korean Music Therapy Students’ Experience of Group Music Therapy: A Qualitative Case Study - So, Hyejin (Frontiers in Psychology, 2019)
The purpose of this qualitative case study is to describe in-depth the experience of Korean students undergoing group music therapy. Seven students participated in eight consecutive weeks of group music therapy. The researcher collected and triangulated three data resources: individual interview transcripts, participant journals, and audiotaped sessions. The data were analyzed using the case study method and peer debriefing was conducted for trustworthiness. The four emergent themes and six categories were as follows: (1) Discovering who I am (categories: what it means to be me, learning about self), (2) Inside group music therapy (categories: it was flowing like water, silence, I can do whatever I want safely here, and the truth of my family), (3) The role of music, and (4) What we learned with books became real. The results indicated that the student therapists’ experiences were linked to their personal development, unique experience of group music therapy dynamics, musical experience as an emotional container, and clinical development. Finally, it is recommended that cultural adaptations are made by providing both structure and space for Korean students to express themselves.